A Reliable and Rapid Language Tool for the Diagnosis, Classification, and Follow-Up of Primary Progressive Aphasia Variants - Epelbaum, Stéphane; Saade, Yasmina Michel; Flamand Roze, Constance; Roze, Emmanuel; Ferrieux, Sophie; Arbizu, Céline; Nogues, Marie; Azuar, Carole; Dubois, Bruno; Tezenas du Montcel, Sophie; Teichmann, Marc (Frontiers in Neurology, 2021)
Background: Primary progressive aphasias (PPA) have been investigated by clinical, therapeutic and fundamental research but examiner-consistent language tests for reliable reproducible diagnosis and follow-up are lacking. Methods: We developed and evaluated a rapid language test for PPA (‘PARIS’) assessing its inter-examiner consistency, its power to detect and classify PPA, and its capacity to identify language decline after a follow-up of 9 months. To explore the reliability and specificity/sensitivity of the test it was applied to PPA patients (N=36), typical amnesic Alzheimer’s disease (AD) patients (N=24) and healthy controls (N=35), while comparing it to two rapid examiner-consistent language tests used in stroke-induced aphasia (‘LAST’, ‘ART’). Results: The application duration of the ‘PARIS’ was approximately 10 minutes and its inter-rater consistency was of 88%. The three tests distinguished healthy controls from AD and PPA patients but only the ‘PARIS’ reliably separated PPA from AD and allowed for classifying the two most frequent PPA variants: semantic and logopenic PPA. Compared to the ‘LAST’ and ‘ART’, the ‘PARIS’ also had the highest sensitivity for detecting language decline. Conclusions: The ‘PARIS’ is an efficient, rapid, and highly examiner-consistent language test for the diagnosis, classification and follow-up of frequent PPA variants. It might also be a valuable tool for providing end-points in future therapeutic trials on PPA and other neurodegenerative diseases affecting language processing.